Discourse errors analysis in ielts writing task 2 answers written by ielts learners in da nang city - Nguyễn Thị Minh Thi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to explore the errors made by English learners in their writing of IELTS writing task 2. It seeks to provide an analysis of these writing errors at the discourse level by looking at the types of errors. In addition, it hopes to provide better insight into possible causes and give suggestions on how to avoid discourse errors.